Survey of Fishing, Hunting, and Wildlife-Associated Recreation, 1980 ([Verlag nicht ermittelbar], 1984)
This three-part survey was conducted in 1980 by the Census Bureau for the Department of the Interior to examine the fishing, hunting, and wildlife-associated activities of United States civilians. Part 1, File FH3, contains information on the kinds of hunting and fishing done. Variables include the state, wildlife region, or foreign country in which the activities occurred, the number of trips taken, duration of trips, distance traveled from home, the average catch or yield, and number of hours per day hunted or fished. Additional information pertains to expenditures for hunting- and fishing-related activities and membership in national or local conservation or wildlife-related organizations. Part 2, File FH4, includes data on wildlife observation, photography, and feeding. Data furnished include type of site visited, type of area (local, state, or federal), kinds of wildlife observed, and expenses for food, lodging, transportation, and fees. Additional information is available on kinds of wildlife present, types and amounts of feed provided, and equipment costs. Part 3, File FH2, supplies information on respondents who participated in fishing, hunting, or nonconsumptive wildlife-associated activities (i.e., wildlife observation, photography, and feeding).